A Deep Web education resources sharing solution different from China e-Learning Technology Standard. (12th May 2011) - Shiming, Zhang; Zhen, Qin; HeXiang, Xu
In the paper, a solution based on Deep Web integration technology is designed to realise the Deep Web education resources sharing and solve the defects of China e-Learning Technology Standard. The solution supports four modules: knowledge discovery, integrated query, knowledge base and system monitor. The former two modules function based on the integration with the later two modules. The design has been applied to an inter-library search system. Four libraries are joined in the system. Good feedback has been received. The project has been awarded the 'Shanghai Science and Technology Progress Third Level Award'. The solution is still preliminary, and there are many aspects to be improved. The future research is supported by Innovation Program of Shanghai Municipal Education Commission.